Pikoela Liwu: Unveiling the Sustainability of Traditional Culture in the Era of Modernization - Puspita Rizki, Dian (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2024)
This study aims to understand the implementation process of the Pikoela Liwu tradition, explore the reasons for its preservation, and analyze the impact of modernization on this tradition in Takimpo Village, Buton Regency. A descriptive qualitative approach was employed, utilizing primary data collected through observations and in-depth interviews with informants selected via snowball sampling, along with secondary data from related documentation. Data analysis was conducted using an interactive analysis model, involving data reduction, data presentation, and conclusion verification. The findings reveal that the Pikoela Liwu tradition is carried out over eight days, featuring a series of rituals including communal prayers, animal sacrifices, the installation of cultural attributes, and traditional dances. The continuity of this tradition is supported by strong community solidarity, ideological resistance to change, and reverence for ancestral cultural values. Modernization has influenced certain aspects, such as population migration, the use of modern materials for traditional house roofs, the shortened duration of rituals, and the replacement of traditional beverages with commercial products. Despite these changes, the tradition remains significant as a symbol of cultural and spiritual identity for the community. This study provides insights into the dynamics of cultural preservation amidst modernization challenges, contributing to the understanding of local cultural sustainability in the era of globalization.